Respuesta :

4a^3 - 6a^2 -a^3 + 3a^2
= 3a^3 - 3a^2

-----------
Simplifying
4a + 3 = 6a + a2

Reorder the terms:
3 + 4a = 6a + a2

Solving
3 + 4a = 6a + a2

Solving for variable 'a'.

Combine like terms: 4a + -6a = -2a
3 + -2a + -1a2 = 6a + a2 + -6a + -1a2

Reorder the terms:
3 + -2a + -1a2 = 6a + -6a + a2 + -1a2

Combine like terms: 6a + -6a = 0
3 + -2a + -1a2 = 0 + a2 + -1a2
3 + -2a + -1a2 = a2 + -1a2

Combine like terms: a2 + -1a2 = 0
3 + -2a + -1a2 = 0

Factor a trinomial.
(1 + -1a)(3 + a) = 0